(untitled) (Homoeopathy for All, 2024)
Alopecia is a condition characterized by hair loss from the scalp or other areas of the body. It is a multifactorial disorder with significant psychological impacts, affecting an individual’s well being and quality of life. Insights from dermatology, genetics, immunology, and endocrinology are vital in understanding this complex condition.